The Effect of Leadership and Organizational Commitment on Employee Performance Mediated by Organizational Culture A Study at PT BPR Kertiawan - Putri, Ni Putu Ayu Aristha Widiani; Putra, Ida Bagus Udayana; Amertha, I Made Suniastha (International Journal of Environmental, Sustainability, and Social Science, 2026)
This study aims to analyze the effects of leadership and organizational commitment on employee performance, with organizational culture serving as a mediating variable at PT BPR Kertiawan. The background of this study is the consistent failure to meet credit disbursement targets since 2020, which indicates underlying issues in employee performance. This research employs a quantitative approach using a survey of employees at PT BPR Kertiawan. Data were analyzed using path analysis through Partial Least Squares (PLS). The results indicate that leadership and organizational commitment have a positive and significant effect on employee performance. In addition, organizational culture has a positive and significant effect on employee performance and is significantly influenced by leadership and organizational commitment. Furthermore, organizational culture has been shown to mediate the effects of leadership and organizational commitment on employee performance. These findings suggest that employee performance can be improved through effective leadership, strengthened organizational commitment, and a supportive organizational culture. This study is expected to contribute theoretically to the development of human resource management literature and provide practical implications for regional banking management in enhancing sustainable employee performance.